Knowledge and attitude towards mental illness among health and non-health university students in Riyadh - Mahboub, Samira M.; Aleyadhi, Rahaf A.; Aldrees, Reema I.; Almuhanna, Shahad S. (International Journal of Research in Medical Sciences, 2020)
Background: Mental illness can affect anyone regardless of age, gender, and residence. Studying the attitude and knowledge about mental illnesses among university students is important, because they are the future decision makers dealing with such problems. The aim of this study was to assess level of knowledge and attitude towards mental illnesses among health and non-health university students in Riyadh. Methods: This study was a cross-sectional study on students of the governmental universities in Riyadh with both health and non-health speciality. The total sample size was 587 students. The questionnaire was designed electronically, and the link was distributed through social media. It included socio-demographic questions, 17 questions to assess knowledge and 22 questions to assess the attitudes. The statistical tests used were chi square, independent sample t-test, spearman’s correlation and multiple linear regression tests. Results: More than half of the participants had a positive attitude toward mental illness (52%). Only 13.46% of university students had good knowledge about mental illness. Significant higher level of good knowledge and positive attitude were reported among health college students compared to non-health (24.7% versus 7.9% for good knowledge and 60.8% versus 48.3 for positive attitude respectively). Attitude towards mental illness can be successfully predicted by using the knowledge score about mental illness and the type of college. Conclusion: Low percentage of university students had good knowledge about mental illness and their attitude towards mental illness was generally positive. Health college students had better attitude and knowledge about mental illness than non-health.